GAMBARAN KONSEP DIRI DAN MEKANISME KOPING REMAJA DI PONDOK PESANTREN - Indriani, Reftesa; Nauli, Fathra Annis; Dewi, Ari Pristiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Youth period for adolescent considered to be unstable and still looking for identity in between its community, then usually adolescent have to be adaptive with the environment in Islamic boarding school. The purpose of this research was to explore the adolescent self-concept and coping mechanism in Islamic Boarding School. This research uses a descriptive method. This research were using 135 adolescents for samples, based on inclusive criteria using stratified random sampling method. This research was located in SMA Babussalam Pekanbaru. This research were using 40 questionnaires for self-concept and 17 for coping mechanism that have been tested by using validity test and reability test. This research were using univariat analyze to explain the frequency table. The final result of this research for selfconcept showed that the samples tend to be positive than negative, 69 adolescent (51.1%) have positive self-concept and 66 adolescent (48.9%) have negative self-concept. Coping mechanism showed that the samples tend to be adaptive than maladaptive, 95 adolescent (70,4%) have adaptive coping mechanism and 40 adolescent (29,6%) have maladaptive coping mechanism. Based on the result of this study, it is suggested to Islamic Boarding School to maintain and developing mentality program, that adolescent tend to have a positive effect for self-concept and improve its counseling to have an adaptive coping mechanism.Keywords: Adolescent, coping mechanism, Islamic Boarding School, self-concept